Incidental Unilateral Tubal Absence Detected During Caesarean Section: Report of a Case - Selçuk Erkılınç; Ali İrfan Güzel; Melike Doğanay; İrfan Özer; Coşkun Ümit (Gynecology Obstetrics & Reproductive Medicine)
Unilateral tubal absence is a rare clinical condition with unknown etiology and probable causes are adnexal torsion, ischemia, birth defects and infection. In the literature there is limited data and only few case reports about this disease. Therefore we aimed to evaluate the clinical characteristics of an incidental unilateral tubal atrophy case during caesarean section that can be considered for publication.